Lutetium hydride film and preparation method thereof
The leutian hydride film is prepared under normal temperature and pressure by pulsed laser deposition method, controlling the properties of hydrogen pressure, solving the problem that leutian hydride film is difficult to stabilize and maintain properties under normal temperature and pressure, and achieving film preparation of various properties and high stability.
Patent Information
- Application Number
- CN202311042546.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-18
- Publication Date
- 2025-02-21
AI Technical Summary
The prior art is difficult to stabilize the preparation of tertium hydride films under normal temperature and pressure, and its physical and chemical properties exhibited by high-pressure environments are difficult to maintain under normal pressure.
A pulsed laser deposition method is used to prepare a letetium hydride film under normal temperature and pressure. By controlling the pressure of the reaction gas hydrogen in the range of 0
Successfully prepared a thirty-hydride film that is stable at normal temperature and pressure, which can exhibit superconducting properties, metal properties, semiconductor properties and insulator properties, and the film has a high stability under nitrogen conditions at normal temperature and pressure and in an air environment. .
Smart Images

Figure CN119491192A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of materials and metal hydride films. Specifically, the present invention relates to a lutetium hydride film and a preparation method thereof. Background Art
[0002] Rare earth metal hydrides have excellent physical and chemical properties, especially the high-temperature superconductivity exhibited by these hydrides under high pressure conditions. [1-6] , prompting people to conduct more in-depth and detailed research on these materials.
[0003] A daunting challenge is whether and how to obtain such rare earth metal hydride samples so that they can exhibit physical and chemical properties similar to those under the aforementioned high-pressure conditions, including superconductivity, under ordinary normal-pressure conditions.
[0004] Recently, it has been reported that lutetium, as the lanthanide metal element with the largest atomic number, nitrogen-doped lutetium hydride [7-8] , and undoped lutetium hydride [9] However, these studies are also controversial, and several other research groups have concluded through their own experimental studies that these lutetium hydrides, whether doped or undoped, do not exhibit superconductivity under high pressure conditions. [10-12] At present, these two diametrically opposed views exist simultaneously.
[0005] Obviously, no matter what the final outcome of the above debate is, that is, whether rare earth metal hydrides are superconducting under high-pressure environmental conditions; whether it is possible to prepare rare earth metal hydride materials that are stable under normal temperature and pressure conditions, it has important scientific and technological and potential production practice application significance.
[0006] Currently, there is an urgent need for a method for preparing a lutetium hydride thin film, which does not require a high-pressure environment during the preparation process and can stably preserve the prepared lutetium hydride thin film at room temperature and pressure. Summary of the invention
[0007] Therefore, the object of the present invention is to provide a method for preparing a lutetium hydride thin film material and a lutetium hydride thin film material prepared by the method. The lutetium hydride thin film prepared by the method of the present invention can be stably stored at room temperature and pressure, and the preparation process of the method of the present invention is simple and does not require a high-pressure environment. In addition, the method of the present invention can prepare lutetium hydride thin films of various properties, such as lutetium hydride thin films with superconducting properties and a superconducting transition at 2.5K to 3K, lutetium hydride thin films with metallic properties, lutetium hydride thin films with semiconductor properties, and lutetium hydride thin films with insulator properties.
[0008] The above-mentioned object of the present invention is achieved through the following technical solutions.
[0009] In the context of the present invention, the deposition device of the present invention can adopt the device disclosed in the prior art, such as the deposition device disclosed in CN202576547U. The thin film deposition device includes a thin film deposition chamber, which includes: a chamber shell, the chamber shell encloses the chamber of the thin film deposition chamber; a target material bracket, which is arranged in the middle of the chamber and is used to place the target material composed of component A; a substrate stage, which is arranged in the middle of the chamber and is arranged opposite to the target material bracket; a laser incident port, which is arranged on the side of the chamber shell and is obliquely opposite to the target material bracket, and is used to incident laser to bombard the target material on the target material bracket to generate plasma plume; a beam source furnace interface, which is arranged on the side of the chamber shell and is obliquely opposite to the substrate stage, and is used to incident a molecular beam composed of component B; the laser incident port and the beam source furnace interface simultaneously incident laser and molecular beam.
[0010] In the context of the present invention, the term "superconducting property" means that the room temperature resistivity of the sample is less than or equal to 1×10 -4 Ωcm, the resistance decreases with decreasing temperature, and a superconducting transition can be observed.
[0011] In the context of the present invention, the term "metallic property" means that the room temperature resistivity of the sample is greater than 1×10 -4 Ωcm and less than or equal to 1×10 -3 Ωcm, the resistance decreases with decreasing temperature, but no superconducting transition is observed in the temperature range from room temperature to 2.5K.
[0012] In the context of the present invention, the term "semiconductor properties" means that the room temperature resistivity of the sample is greater than 1×10 -3 Ωcm and less than or equal to 1×10 6 Ωcm.
[0013] In the context of the present invention, the term "insulator property" means that the room temperature resistivity of the sample is greater than 1×10 6 Ωcm.
[0014] In the context of the present invention, the term "Residual Resistivity Ratio (RRR)" refers to the ratio of the resistivity of a sample at the lowest temperature measured by RT (usually around 2.5 K in this article) to its resistivity at room temperature.
[0015] In one aspect, the present invention provides a method for preparing a lutetium hydride thin film, comprising the following steps:
[0016] (1) placing a lutetium metal target in a thin film deposition chamber;
[0017] (2) cleaning the substrate, and then mounting the cleaned substrate on a substrate stage;
[0018] (3) Then, heating the substrate stage and thereby heating the substrate;
[0019] (4) introducing hydrogen into the thin film deposition chamber and controlling the gas pressure in the thin film deposition chamber to be P, wherein 0<P≤5Pa;
[0020] (5) Then, a lutetium hydride thin film material is grown on the substrate by a pulsed laser deposition method; after the deposition is completed, the sample is allowed to cool naturally to room temperature to obtain a lutetium hydride thin film LuH X , where 0<x≤3.
[0021] The inventors of the present application unexpectedly discovered that by using the pulsed laser deposition method for the preparation of lutetium hydride thin film materials while controlling the pressure of the reaction gas hydrogen within an appropriate range, lutetium hydride thin film materials with various properties, such as superconducting properties, metallic properties, semiconductor properties, insulating properties, etc., can be prepared.
[0022] The inventors of the present application also unexpectedly discovered that when the chamber pressure during pulse laser deposition is controlled within the range of 0<P≤2×10 -4 Pa, the prepared lutetium hydride film LuH X It has superconducting properties and there is a superconducting transition between 2.5K and 3K.
[0023] Preferably, in the method described in the present invention, the lutetium metal target is a polycrystalline single-element lutetium target.
[0024] Preferably, in the method described in the present invention, the purity of the polycrystalline single-substance lutetium target is >99.99%.
[0025] Preferably, in the method described in the present invention, the substrate is a (001) oriented LaAlO3 single crystal substrate or a (001) oriented Si single crystal substrate.
[0026] Preferably, in the method of the present invention, the cleaning of the substrate in step (2) is performed by a method comprising the following steps: ultrasonically cleaning the substrate with acetone and alcohol for 3-5 minutes respectively.
[0027] Preferably, in the method of the present invention, after step (2) and before step (3), the method further comprises the following steps: adjusting the height of the substrate stage so that the distance between the target and the substrate is 1.8-4 cm; and evacuating the thin film deposition chamber so that the vacuum degree in the thin film deposition chamber is higher than 1×10 -6 Pa.
[0028] Preferably, in the method of the present invention, the heating of the substrate stage in step (3) is performed by heating the temperature of the substrate to a target temperature of 500-650°C at a heating rate of 10-30°C / min.
[0029] Preferably, in the method described in the present invention, after step (4) and before step (5), the method further comprises the following steps: blocking the substrate with a baffle, and then pre-sputtering the target surface with a pulsed laser, wherein the number of pulses is 600-1200.
[0030] Preferably, in the method of the present invention, the pulse laser deposition method in step (5) is carried out under the following conditions: the energy density of the pulse laser is 120-180 mJ / mm 2 , the laser repetition frequency is 1-8Hz.
[0031] Preferably, in the method of the present invention, when 0<P≤2×10 -4 Pa, the prepared lutetium hydride film LuH X It has superconducting properties and there is a superconducting transition between 2.5K and 3K.
[0032] Preferably, in the method of the present invention, when 2×10 -4 Pa<P≤1×10 -3 Pa, the prepared lutetium hydride film LuH X Has metallic properties.
[0033] Preferably, in the method of the present invention, when 1×10 -3 When Pa<P≤1Pa, the prepared lutetium hydride film has semiconductor properties.
[0034] Preferably, in the method of the present invention, when 1Pa<P≤5Pa, the prepared lutetium hydride film has insulating properties.
[0035] Preferably, in the method of the present invention, the room temperature resistivity of the prepared lutetium hydride film increases monotonically with the increase of the deposition pressure P. Therefore, it is reasonable to infer that when P>5Pa, the prepared lutetium hydride film still has the properties of an insulator. Further increasing the pressure will cause a significant change in various state parameters during the film deposition process, which will increase the preparation cost and difficulty. Therefore, it is preferred in the present invention that the chamber pressure P≤5Pa.
[0036] In another aspect, the present invention provides a lutetium hydride film prepared by the method of the present invention, wherein the composition is represented by the following chemical formula: LuH X , where 0<x≤3.
[0037] The present invention has the following beneficial effects:
[0038] (1) The method of the present invention can prepare a lutetium hydride thin film material that is stable at room temperature and pressure. The chemical formula of the thin film material is: LuH x , where 0<x≤3, and by adjusting the gas pressure during film preparation, thin films with different properties such as superconducting properties, metallic properties, semiconductor properties, and insulating properties can be prepared, which can be used to study their physical properties.
[0039] (2) The present invention can directly prepare lutetium hydride thin film materials without going through any intermediate steps and intermediate states, that is, no additional treatments such as post-annealing treatment and high-pressure gas reaction are required.
[0040] (3) The present invention adopts a pulsed laser deposition method to prepare a lutetium hydride thin film material that is stable at room temperature and pressure and has a superconducting transition temperature of 2.5K to 3K, which effectively reduces the difficulty of preparing lutetium hydride superconducting materials and provides a method and direction for exploring rare earth hydride superconducting materials.
[0041] (4) The lutetium hydride thin film material prepared by the method of the present invention has high stability under nitrogen conditions at room temperature and pressure and in an air environment. The thin film with superconducting properties, which is most susceptible to environmental influences, was stored in a N2 protective atmosphere at room temperature and pressure for 60 days and exposed to an air environment for about ten hours. The morphology, structure, and electrical transport properties of the sample did not change significantly. The superconducting transition was still observed in the RT measurement, and the superconducting transition temperature did not change significantly. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] The embodiments of the present invention are described in detail below with reference to the accompanying drawings, wherein:
[0043] Figure 1 This is a sample photo of the lutetium hydride thin film material prepared according to Example 1 of the present invention at room temperature and pressure.
[0044] Figure 2 This is a full X-ray diffraction spectrum of the lutetium hydride thin film material prepared according to Example 1 of the present invention.
[0045] Figure 3 RT curve of the lutetium hydride thin film material prepared according to Example 1 of the present invention, with an applied current of 10 μA.
[0046] Figure 4 This is a full X-ray diffraction spectrum of the lutetium hydride thin film material prepared according to Example 2 of the present invention.
[0047] Figure 5RT curve of the lutetium hydride thin film material prepared according to Example 2 of the present invention, with an applied current of 10 μA.
[0048] Figure 6 This is a full X-ray diffraction spectrum of the lutetium hydride thin film material prepared according to Example 3 of the present invention.
[0049] Figure 7 RT curve of the lutetium hydride thin film material prepared according to Example 3 of the present invention, with an applied current of 10 μA.
[0050] Figure 8 This is a full X-ray diffraction spectrum of the lutetium hydride thin film material prepared according to Example 4 of the present invention.
[0051] Fig. 9 RT curve of the lutetium hydride thin film material prepared according to Example 4 of the present invention, with an applied current of 10 μA.
[0052] Fig.10 This is a full X-ray diffraction spectrum of the lutetium hydride thin film material prepared according to Example 5 of the present invention.
[0053] Fig.11 RT curve of the lutetium hydride thin film material prepared according to Example 5 of the present invention, with an applied current of 10 μA.
[0054] Fig.12 This is a full X-ray diffraction spectrum of the lutetium hydride thin film material prepared according to Example 6 of the present invention.
[0055] Fig.13 RT curve of the lutetium hydride thin film material prepared according to Example 6 of the present invention, with an applied current of 10 μA.
[0056] Fig.14 This is a full X-ray diffraction spectrum of the lutetium hydride thin film material prepared according to Example 7 of the present invention.
[0057] Fig.15 This is a full X-ray diffraction spectrum of the lutetium hydride thin film material prepared according to Example 8 of the present invention.
[0058] Fig.16 This is a full X-ray diffraction spectrum of the lutetium hydride thin film material prepared according to Example 9 of the present invention.
[0059] Fig.17 This is a full X-ray diffraction spectrum of the lutetium hydride thin film material prepared according to Example 10 of the present invention.
[0060] Fig.18RT curve of the lutetium hydride thin film material prepared according to Example 10 of the present invention, with an applied current of 10 μA.
[0061] Fig.19 This is a sample photo of the lutetium hydride thin film material in Example 11 of the present invention at room temperature and pressure.
[0062] Fig. 20 This is the full X-ray diffraction spectrum of the lutetium hydride thin film material in Example 11 of the present invention.
[0063] Fig.21 RT curve of the lutetium hydride thin film material in Example 11 of the present invention, with an applied current of 10 μA.
[0064] Fig. 22 This is the full X-ray diffraction spectrum of the lutetium thin film material prepared according to Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0065] The present invention is further described in detail below in conjunction with specific embodiments. The given examples are only for illustrating the present invention, but not for limiting the scope of the present invention.
[0066] In the following specific embodiments of the present invention, regarding the prepared LuH x The x value in the film is determined by the following calculation method:
[0067] The XRD diffraction spectrum of the sample prepared according to the present invention shows LuH x The corresponding peak position is used to calculate the LuH x The lattice constant of LuH2 is then compared with the known lattice constants of LuH3 according to Vegard's law (refer to the prior art Vegard L.Die Konstitution derMischkristalle und die Raumfüllung der Atome.Z.Physik 5,17-26(1921)), and the value of x is determined by interpolation.
[0068] Example 1
[0069] (1) Prepare a lutetium metal target (polycrystalline) and fix it on a target holder, and then install the target holder into a thin film deposition chamber.
[0070] (2) Prepare a (001) oriented LaAlO3 single crystal substrate, clean it with acetone and alcohol ultrasonically for 5 minutes, and then blow dry it with compressed nitrogen. Then, install the substrate on the substrate stage through the feed port. Then adjust the position of the substrate stage so that the target is directly below the substrate and the distance between the target and the substrate is controlled to be about 1.9 cm.
[0071] (3) Turn on the multi-stage vacuum pump group. When the vacuum degree of the chamber is better than 1×10 -6 Pa, start heating the substrate stage and heat the substrate to 600°C at a heating rate of 10°C / min.
[0072] (4) Keep the multi-stage vacuum pump group turned on, turn on the gas flow meter to control the gas flow, and maintain the dynamic equilibrium pressure of hydrogen in the chamber at 1×10 -5 Pa.
[0073] (5) After the gas pressure stabilizes, block the substrate with a baffle, and then pre-sputter the target surface with a pulsed laser, with the number of pulses being about 600.
[0074] (6) After the pre-sputtering is completed, the baffle is removed to allow the pulse laser to bombard the target material, and the resulting plasma plume is deposited on the substrate, that is, a lutetium hydride thin film material is grown on the substrate by a pulse laser deposition method. The deposition pulse frequency is 5 Hz and the deposition time is 100 min.
[0075] (7) After the film deposition is completed, turn off the heater and gas flow meter to allow the film to cool naturally to room temperature in a vacuum environment.
[0076] The photo of the sample of the lutetium hydride thin film material prepared in this example at room temperature and pressure is shown in FIG. Figure 1 Its XRD diffraction pattern is shown in Figure 2 As shown, the lutetium hydride film LuH obtained in this embodiment can be calculated. X In the figure, x = 2.0. The RT test results of this sample are as follows Figure 3 As shown, it can be concluded that the sample has superconducting properties, the superconducting transition temperature is 2.5K, and the room temperature resistivity is 3.2×10 -5 Ωcm, and the residual resistivity ratio is 22.5%. The above experiments were all carried out within three days after the film deposition was completed.
[0077] Example 2
[0078] (1) Prepare a lutetium metal target (polycrystalline) and fix it on a target holder, and then install the target holder into a thin film deposition chamber.
[0079] (2) Prepare a (001) oriented LaAlO3 single crystal substrate, clean it with acetone and alcohol ultrasonically for 5 minutes, and then blow dry it with compressed nitrogen. Then, install the substrate on the substrate stage through the feed port. Then adjust the position of the substrate stage so that the target is directly below the substrate and the distance between the target and the substrate is controlled to be about 1.9 cm.
[0080] (3) Turn on the multi-stage vacuum pump group. When the vacuum degree of the chamber is better than 1×10 -6Pa, start heating the substrate stage and heat the substrate to 600°C at a heating rate of 10°C / min.
[0081] (4) Keep the multi-stage vacuum pump group turned on, turn on the gas flow meter to control the gas flow, and maintain the dynamic equilibrium pressure of hydrogen in the chamber at 1×10 -4 Pa.
[0082] (5) After the gas pressure stabilizes, block the substrate with a baffle, and then pre-sputter the target surface with a pulsed laser, with the number of pulses being about 600.
[0083] (6) After the pre-sputtering is completed, the baffle is removed to allow the pulse laser to bombard the target material, and the resulting plasma plume is deposited on the substrate, that is, a lutetium hydride thin film material is grown on the substrate by a pulse laser deposition method. The deposition pulse frequency is 5 Hz and the deposition time is 100 min.
[0084] (7) After the film deposition is completed, turn off the heater and gas flow meter to allow the film to cool naturally to room temperature in a vacuum environment.
[0085] The XRD diffraction pattern of the sample of the lutetium hydride thin film material prepared in this embodiment is as follows: Figure 4 As shown, the lutetium hydride film LuH obtained in this embodiment can be calculated. X In the figure, x = 2.0. The RT test results of this sample are as follows Figure 5 As shown, it can be concluded that the sample has superconducting properties, the superconducting transition temperature is 3K, and the room temperature resistivity is 2.5×10 -5 Ωcm, and the residual resistivity ratio is 24.4%. The above experiments were all carried out within three days after the film deposition was completed.
[0086] Example 3
[0087] (1) Prepare a lutetium metal target (polycrystalline) and fix it on a target holder, and then install the target holder into a thin film deposition chamber.
[0088] (2) Prepare a (001) oriented LaAlO3 single crystal substrate, clean it with acetone and alcohol ultrasonically for 5 minutes, and then blow dry it with compressed nitrogen. Then, install the substrate on the substrate stage through the feed port. Then adjust the position of the substrate stage so that the target is directly below the substrate and the distance between the target and the substrate is controlled to be about 1.9 cm.
[0089] (3) Turn on the multi-stage vacuum pump group. When the vacuum degree of the chamber is better than 1×10 -6 Pa, start heating the substrate stage and heat the substrate to 600°C at a heating rate of 10°C / min.
[0090] (4) Keep the multi-stage vacuum pump group turned on, turn on the gas flow meter to control the gas flow, and maintain the dynamic equilibrium pressure of hydrogen in the chamber at 2×10 -4 Pa.
[0091] (5) After the gas pressure stabilizes, block the substrate with a baffle, and then pre-sputter the target surface with a pulsed laser, with the number of pulses being about 600.
[0092] (6) After the pre-sputtering is completed, the baffle is removed to allow the pulse laser to bombard the target material, and the resulting plasma plume is deposited on the substrate, that is, a lutetium hydride thin film material is grown on the substrate by a pulse laser deposition method. The deposition pulse frequency is 5 Hz and the deposition time is 100 min.
[0093] (7) After the film deposition is completed, turn off the heater and gas flow meter to allow the film to cool naturally to room temperature in a vacuum environment.
[0094] The XRD diffraction pattern of the sample of the lutetium hydride thin film material prepared in this embodiment is as follows: Figure 6 As shown, the lutetium hydride film LuH obtained in this embodiment can be calculated. X In the figure, x = 2.0. The RT test results of this sample are as follows Figure 7 As shown, it can be concluded that the sample has superconducting properties, the superconducting transition temperature is 2.5K, and the room temperature resistivity is 3.0×10 -5 Ωcm, and the residual resistivity ratio is 29.2%. The above experiments were all carried out within three days after the film deposition was completed.
[0095] Example 4
[0096] (1) Prepare a lutetium metal target (polycrystalline) and fix it on a target holder, and then install the target holder into a thin film deposition chamber.
[0097] (2) Prepare a (001) oriented LaAlO3 single crystal substrate, clean it with acetone and alcohol ultrasonically for 5 minutes, and then blow dry it with compressed nitrogen. Then, install the substrate on the substrate stage through the feed port. Then adjust the position of the substrate stage so that the target is directly below the substrate and the distance between the target and the substrate is controlled to be about 1.9 cm.
[0098] (3) Turn on the multi-stage vacuum pump group. When the vacuum degree of the chamber is better than 1×10 -6 Pa, start heating the substrate stage and heat the substrate to 600°C at a heating rate of 10°C / min.
[0099] (4) Keep the multi-stage vacuum pump group turned on, turn on the gas flow meter to control the gas flow, and maintain the dynamic equilibrium pressure of hydrogen in the chamber at 3×10 -4 Pa.
[0100] (5) After the gas pressure stabilizes, block the substrate with a baffle, and then pre-sputter the target surface with a pulsed laser, with the number of pulses being about 600.
[0101] (6) After the pre-sputtering is completed, the baffle is removed to allow the pulse laser to bombard the target material, and the resulting plasma plume is deposited on the substrate, that is, a lutetium hydride thin film material is grown on the substrate by a pulse laser deposition method. The deposition pulse frequency is 5 Hz and the deposition time is 100 min.
[0102] (7) After the film deposition is completed, turn off the heater and gas flow meter to allow the film to cool naturally to room temperature in a vacuum environment.
[0103] The XRD diffraction pattern of the sample of the lutetium hydride thin film material prepared in this embodiment is as follows: Figure 8 As shown, the lutetium hydride film LuH obtained in this embodiment can be calculated. X In the figure, x = 2.0. The RT test results of this sample are as follows Fig. 9 As shown, it can be concluded that the sample has metallic properties and the room temperature resistivity is 1.6×10 -4 Ωcm, and the residual resistivity ratio is 47.5%. The above experiments were all carried out within three days after the film deposition was completed.
[0104] Example 5
[0105] (1) Prepare a lutetium metal target (polycrystalline) and fix it on a target holder, and then install the target holder into a thin film deposition chamber.
[0106] (2) Prepare a (001) oriented LaAlO3 single crystal substrate, clean it with acetone and alcohol ultrasonically for 5 minutes, and then blow dry it with compressed nitrogen. Then, install the substrate on the substrate stage through the feed port. Then adjust the position of the substrate stage so that the target is directly below the substrate and the distance between the target and the substrate is controlled to be about 1.9 cm.
[0107] (3) Turn on the multi-stage vacuum pump group. When the vacuum degree of the chamber is better than 1×10 -6 Pa, start heating the substrate stage and heat the substrate to 600°C at a heating rate of 10°C / min.
[0108] (4) Keep the multi-stage vacuum pump group turned on, turn on the gas flow meter to control the gas flow, and maintain the dynamic equilibrium pressure of hydrogen in the chamber at 8×10 -4 Pa.
[0109] (5) After the gas pressure stabilizes, block the substrate with a baffle, and then pre-sputter the target surface with a pulsed laser, with the number of pulses being about 600.
[0110] (6) After the pre-sputtering is completed, the baffle is removed to allow the pulse laser to bombard the target material, and the resulting plasma plume is deposited on the substrate, that is, a lutetium hydride thin film material is grown on the substrate by a pulse laser deposition method. The deposition pulse frequency is 5 Hz and the deposition time is 100 min.
[0111] (7) After the film deposition is completed, turn off the heater and gas flow meter to allow the film to cool naturally to room temperature in a vacuum environment.
[0112] The XRD diffraction pattern of the sample of the lutetium hydride thin film material prepared in this embodiment is as follows: Fig.10 As shown, the lutetium hydride film LuH obtained in this embodiment can be calculated. X In the figure, x = 2.0. The RT test results of this sample are as follows Fig.11 As shown, it can be concluded that the sample has metallic properties and the room temperature resistivity is 8.8×10 -4 Ωcm, and the residual resistivity ratio is 92.3%. The above experiments were all carried out within three days after the film deposition was completed.
[0113] Example 6
[0114] (1) Prepare a lutetium metal target (polycrystalline) and fix it on a target holder, and then install the target holder into a thin film deposition chamber.
[0115] (2) Prepare a (001) oriented LaAlO3 single crystal substrate, clean it with acetone and alcohol ultrasonically for 5 minutes, and then blow dry it with compressed nitrogen. Then, install the substrate on the substrate stage through the feed port. Then adjust the position of the substrate stage so that the target is directly below the substrate and the distance between the target and the substrate is controlled to be about 1.9 cm.
[0116] (3) Turn on the multi-stage vacuum pump group. When the vacuum degree of the chamber is better than 1×10 -6 Pa, start heating the substrate stage and heat the substrate to 600°C at a heating rate of 10°C / min.
[0117] (4) Keep the multi-stage vacuum pump group turned on, turn on the gas flow meter to control the gas flow, and maintain the dynamic equilibrium pressure of hydrogen in the chamber at 5×10 -3 Pa.
[0118] (5) After the gas pressure stabilizes, block the substrate with a baffle, and then pre-sputter the target surface with a pulsed laser, with the number of pulses being about 600.
[0119] (6) After the pre-sputtering is completed, the baffle is removed to allow the pulse laser to bombard the target material, and the resulting plasma plume is deposited on the substrate, that is, a lutetium hydride thin film material is grown on the substrate by a pulse laser deposition method. The deposition pulse frequency is 5 Hz and the deposition time is 100 min.
[0120] (7) After the film deposition is completed, turn off the heater and gas flow meter to allow the film to cool naturally to room temperature in a vacuum environment.
[0121] The XRD diffraction pattern of the lutetium hydride thin film material prepared in this embodiment is as follows: Fig.12 As shown, the lutetium hydride film LuH obtained in this embodiment can be calculated. X In the figure, x = 2.3. The RT test results of this sample are as follows Fig.13 As shown, it can be concluded that the sample has semiconductor properties and the room temperature resistivity is 5.9×10 -3 Ωcm, and the residual resistivity ratio is 203.9%. The above experiments were all carried out within three days after the film deposition was completed.
[0122] Example 7
[0123] (1) Prepare a lutetium metal target (polycrystalline) and fix it on a target holder, and then install the target holder into a thin film deposition chamber.
[0124] (2) Prepare a (001) oriented LaAlO3 single crystal substrate, clean it with acetone and alcohol ultrasonically for 5 minutes, and then blow dry it with compressed nitrogen. Then, install the substrate on the substrate stage through the feed port. Then adjust the position of the substrate stage so that the target is directly below the substrate and the distance between the target and the substrate is controlled to be about 1.9 cm.
[0125] (3) Turn on the multi-stage vacuum pump group. When the vacuum degree of the chamber is better than 1×10 -6 Pa, start heating the substrate stage and heat the substrate to 600°C at a heating rate of 10°C / min.
[0126] (4) Keep the multi-stage vacuum pump group turned on, turn on the gas flow meter to control the gas flow, and maintain the dynamic equilibrium pressure of hydrogen in the chamber at 0.5Pa.
[0127] (5) After the gas pressure stabilizes, block the substrate with a baffle, and then pre-sputter the target surface with a pulsed laser, with the number of pulses being about 600.
[0128] (6) After the pre-sputtering is completed, the baffle is removed to allow the pulse laser to bombard the target material, and the resulting plasma plume is deposited on the substrate, that is, a lutetium hydride thin film material is grown on the substrate by a pulse laser deposition method. The deposition pulse frequency is 5 Hz and the deposition time is 100 min.
[0129] (7) After the film deposition is completed, turn off the heater and gas flow meter to allow the film to cool naturally to room temperature in a vacuum environment.
[0130] The XRD diffraction pattern of the lutetium hydride thin film material prepared in this embodiment is as follows: Fig.14As shown, the lutetium hydride film LuH obtained in this embodiment can be calculated. X In this case, x = 2.4. This sample has semiconductor properties, and the room temperature resistivity is about 5×10 5 Ωcm, making it difficult to measure electrical transport properties. The above experiments were all carried out within three days after the film deposition was completed.
[0131] Example 8
[0132] (1) Prepare a lutetium metal target (polycrystalline) and fix it on a target holder, and then install the target holder into a thin film deposition chamber.
[0133] (2) Prepare a (001) oriented LaAlO3 single crystal substrate, clean it with acetone and alcohol ultrasonically for 5 minutes, and then blow dry it with compressed nitrogen. Then, install the substrate on the substrate stage through the feed port. Then adjust the position of the substrate stage so that the target is directly below the substrate and the distance between the target and the substrate is controlled to be about 1.9 cm.
[0134] (3) Turn on the multi-stage vacuum pump group. When the vacuum degree of the chamber is better than 1×10 -6 Pa, start heating the substrate stage and heat the substrate to 600°C at a heating rate of 10°C / min.
[0135] (4) Keep the multi-stage vacuum pump group turned on, turn on the gas flow meter to control the gas flow, and maintain the dynamic equilibrium pressure of hydrogen in the chamber at 2Pa.
[0136] (5) After the gas pressure stabilizes, block the substrate with a baffle, and then pre-sputter the target surface with a pulsed laser, with the number of pulses being about 600.
[0137] (6) After the pre-sputtering is completed, the baffle is removed to allow the pulse laser to bombard the target material, and the resulting plasma plume is deposited on the substrate, that is, a lutetium hydride thin film material is grown on the substrate by a pulse laser deposition method. The deposition pulse frequency is 5 Hz and the deposition time is 100 min.
[0138] (7) After the film deposition is completed, turn off the heater and gas flow meter to allow the film to cool naturally to room temperature in a vacuum environment.
[0139] The XRD diffraction pattern of the lutetium hydride thin film material prepared in this embodiment is as follows: Fig.15 As shown, the lutetium hydride film LuH obtained in this embodiment can be calculated. X In this case, x = 2.7. This sample has insulating properties, and its room temperature resistivity is about 2×10 6 Ωcm, making it difficult to measure electrical transport properties. The above experiments were all carried out within three days after the film deposition was completed.
[0140] Example 9
[0141] (1) Prepare a lutetium metal target (polycrystalline) and fix it on a target holder, and then install the target holder into a thin film deposition chamber.
[0142] (2) Prepare a (001) oriented LaAlO3 single crystal substrate, clean it with acetone and alcohol ultrasonically for 5 minutes, and then blow dry it with compressed nitrogen. Then, install the substrate on the substrate stage through the feed port. Then adjust the position of the substrate stage so that the target is directly below the substrate and the distance between the target and the substrate is controlled to be about 1.9 cm.
[0143] (3) Turn on the multi-stage vacuum pump group. When the vacuum degree of the chamber is better than 1×10 -6 Pa, start heating the substrate stage and heat the substrate to 600°C at a heating rate of 10°C / min.
[0144] (4) Keep the multi-stage vacuum pump group turned on, turn on the gas flow meter to control the gas flow, and maintain the dynamic equilibrium pressure of hydrogen in the chamber at 5Pa.
[0145] (5) After the gas pressure stabilizes, block the substrate with a baffle, and then pre-sputter the target surface with a pulsed laser, with the number of pulses being about 600.
[0146] (6) After the pre-sputtering is completed, the baffle is removed to allow the pulse laser to bombard the target material, and the resulting plasma plume is deposited on the substrate, that is, a lutetium hydride thin film material is grown on the substrate by a pulse laser deposition method. The deposition pulse frequency is 5 Hz and the deposition time is 100 min.
[0147] (7) After the film deposition is completed, turn off the heater and gas flow meter to allow the film to cool naturally to room temperature in a vacuum environment.
[0148] The XRD diffraction pattern of the lutetium hydride thin film material prepared in this embodiment is as follows: Fig.16 As shown, the lutetium hydride film LuH obtained in this embodiment can be calculated. X In this case, x = 2.9. This sample has insulating properties, and its room temperature resistivity is about 1×10 8 Ωcm, making it difficult to measure electrical transport properties.
[0149] According to the phenomena of Example 8 and Example 9, it can be inferred that when the air pressure is further increased, the room temperature resistivity of the sample will also increase further, which will be detrimental to the measurement of electrical transport properties. Further increasing the air pressure will cause significant changes in various state parameters during the thin film deposition process, which will increase the preparation cost and difficulty. Therefore, it is preferred that the chamber air pressure P≤5Pa. The above experiments were all carried out within three days after the thin film deposition was completed.
[0150] Example 10
[0151] (1) Prepare a lutetium metal target (polycrystalline) and fix it on a target holder, and then install the target holder into a thin film deposition chamber.
[0152] (2) Prepare a (001) oriented LaAlO3 single crystal substrate, clean it with acetone and alcohol ultrasonically for 5 minutes, and then blow dry it with compressed nitrogen. Then, install the substrate on the substrate stage through the feed port. Then adjust the position of the substrate stage so that the target is directly below the substrate and the distance between the target and the substrate is controlled to be about 1.9 cm.
[0153] (3) Turn on the multi-stage vacuum pump group. When the vacuum degree of the chamber is better than 1×10 -6 Pa, start heating the substrate stage and heat the substrate to 550°C at a heating rate of 10°C / min.
[0154] (4) Keep the multi-stage vacuum pump group turned on, turn on the gas flow meter to control the gas flow, and maintain the dynamic equilibrium pressure of hydrogen in the chamber at 3×10 -4 Pa.
[0155] (5) After the gas pressure stabilizes, block the substrate with a baffle, and then pre-sputter the target surface with a pulsed laser, with the number of pulses being about 600.
[0156] (6) After the pre-sputtering is completed, the baffle is removed to allow the pulse laser to bombard the target material, and the resulting plasma plume is deposited on the substrate, that is, a lutetium hydride thin film material is grown on the substrate by a pulse laser deposition method. The deposition pulse frequency is 5 Hz and the deposition time is 100 min.
[0157] (7) After the film deposition is completed, turn off the heater and gas flow meter to allow the film to cool naturally to room temperature in a vacuum environment.
[0158] The XRD diffraction pattern of the lutetium hydride thin film material prepared in this embodiment is as follows: Fig.17 As shown, the lutetium hydride film LuH obtained in this embodiment can be calculated. X In the figure, x = 2.0. The RT test results of this sample are as follows Fig.18 As shown, it can be concluded that the sample has metallic properties and the room temperature resistivity is 1.6×10 -4 Ωcm, and the residual resistivity ratio is 51.6%. The above experiments were all carried out within three days after the film deposition was completed.
[0159] Embodiment 11
[0160] Stability test
[0161] It is well known in the art that thin film materials with superconducting properties are most susceptible to environmental influences and denaturation. Therefore, this example examines the stability of the lutetium hydride thin film material with superconducting properties prepared in Example 1 of the present invention.
[0162] After the lutetium hydride thin film material prepared in Example 1 completes the test described in Example 1, it is placed in a N2 protective atmosphere (water and oxygen content are both less than 0.1ppm) at room temperature and pressure for 60 days, and the N2 environment and room temperature and pressure conditions are maintained during the storage process.
[0163] After 60 days, the sample was taken out of the protective atmosphere and exposed to air for about 10 hours. Then, it was photographed again, XRD measured, and RT measured. The experimental results were compared with the results in Example 1 to verify the stability of the sample under nitrogen conditions at room temperature and pressure and in air.
[0164] The photos of the samples obtained in this example at room temperature and pressure are as follows Fig.19 As shown, the gold dots in the figure are gold electrodes deposited for the RT measurement described in Example 1. Compared with the results obtained in Example 1, the color, gloss and surface morphology of the sample did not change significantly under optical microscope observation, indicating the stability of the sample morphology under nitrogen conditions at room temperature and pressure and in an air environment.
[0165] The XRD diffraction results obtained in this example are as follows Fig. 20 As shown, it can be calculated that the lutetium hydride film LuH X In the figure, x = 2.0. Compared with the results obtained in Example 1, the peak positions and intensities of the sample peaks have no significant changes, which indicates the stability of the sample structure under nitrogen conditions at room temperature and pressure and in an air environment.
[0166] The RT test results obtained in this embodiment are as follows Fig.21 As shown, it can be seen that the sample has superconducting properties, the superconducting transition temperature is 2.5K, and the room temperature resistivity is 3.2×10 -5 Ωcm, and the residual resistivity ratio is 22.6%. Compared with the results obtained in Example 1, the superconducting transition temperature, resistivity, and residual resistivity ratio of the sample have no significant changes, which shows that the electrical transport properties of the sample are stable under nitrogen conditions at room temperature and pressure and in an air environment.
[0167] This example demonstrates that the superconducting film, which is most susceptible to environmental influences, has good stability under nitrogen conditions at room temperature and pressure and in an air environment. Thus, it can be shown that the other film materials prepared in Examples 2-10 of the present invention have good stability under nitrogen conditions at room temperature and pressure and in an air environment.
[0168] Comparative Example 1
[0169] A lutetium thin film was prepared according to the method of Example 1, the only difference from Example 1 being that no reaction gas was introduced in step (4), i.e., the dynamic equilibrium pressure of H2 was 0Pa.
[0170] The XRD diffraction pattern of the lutetium thin film material prepared in this comparative example is as follows: Fig. 22 As shown, no diffraction peaks of LuH2 or LuH3 were observed.
[0171] References
[0172] [1]Drozdov APet al.Superconductivity at 250K in lanthanum hydrideunder high pressures.Nature 569,528-531(2019).
[0173] [2]Kong P. et al. Superconductivity up to 243K in the yttrium-hydrogensystem under high pressure. Nat. Commun. 12, 5075 (2021).
[0174] [3]Snider E.et al.Synthesis of yttrium superhydride superconductorwith a transition temperature up to 262K by catalytic hydrogenation at highpressures.Phys.Rev.Lett.126,117003(2021).
[0175] [4]Chen W.et al.High-temperature superconducting phases in ceriumsuperhydride with a Tc up to 115K below a pressure of1megabar.Phys.Rev.Lett.127,117001(2021).
[0176] [5]D.Zhou et al.Superconducting praseodymium superhydrides.Sci.Adv.6,8(2020),arXiv:1904.06643.
[0177] [6]D.Zhou et al.High-Pressure Synthesis of Magnetic NeodymiumPolyhydrides.J.Am.Chem.Soc.142,2803-2811(2020).
[0178] [7]Dasenbrock-Gammon.et al.Evidence of near-ambient superconductivityin a N-doped lutetium hydride.Nature 615,244-250(2023).
[0179] [8]Nilesh P.S.et al.Evidence for Near Ambient Superconductivity inthe Lu-N-H System.arXiv:2306.06301.
[0180] [9]Li Z.et al.Superconductivity above 70 K observed in lutetiumpolyhydrides.Sci.China Phys.Mech.Astron.66,267411(2023).
[0181]
[10] Shan P.et al.Pressure-Induced Color Change in the LutetiumDihydride LuH2.Chinese Phys.Lett.40,046101(2023).
[0182]
[11] Ming X.et al.Absence of near-ambient superconductivity in LuH2±xNy.Nature 620,72-77(2023).
[0183]
[12] Peng D.et al.The near room-temperature upsurge of electricalresistivity in Lu-H-N is not superconductivity,but a metal-to-poor-conductortransition.arXiv:2307.00201。
Claims
1. A method for preparing a lutetium hydride thin film, comprising the following steps: (1) placing a lutetium metal target in a thin film deposition chamber; (2) cleaning the substrate, and then mounting the cleaned substrate on a substrate stage; (3) Then, heating the substrate stage and thereby heating the substrate; (4) introducing hydrogen into the thin film deposition chamber and controlling the gas pressure in the thin film deposition chamber to be P, wherein 0<P≤5Pa; (5) Then, a lutetium hydride thin film material is grown on the substrate by a pulsed laser deposition method; after the deposition is completed, the sample is allowed to cool naturally to room temperature to obtain a lutetium hydride thin film LuH X , where 0<x≤3.
2. The method according to claim 1, wherein: The lutetium metal target is a polycrystalline single-substance lutetium target; preferably, the purity of the polycrystalline single-substance lutetium target is greater than 99.99%; Preferably, the substrate is a (001) oriented LaAlO3 single crystal substrate or a (001) oriented Si single crystal substrate; Preferably, the cleaning of the substrate in step (2) is performed by a method comprising the following steps: ultrasonically cleaning the substrate with acetone and alcohol for 3-5 minutes respectively.
3. The method according to claim 1, wherein: After step (2) and before step (3), the method further comprises the following steps: Adjust the height of the substrate stage so that the distance between the target and the substrate is 1.8-4 cm; and evacuate the thin film deposition chamber so that the vacuum degree in the thin film deposition chamber is higher than 1×10 -6 Pa.
4. The method according to claim 1, wherein: The heating of the substrate stage in the step (3) is performed by heating the temperature of the substrate to a target temperature of 500-650° C. at a heating rate of 10-30° C. / min.
5. The method according to claim 1, wherein: After step (4) and before step (5), the method further comprises the following steps: The substrate is blocked with a baffle, and then the target surface is pre-sputtered with a pulsed laser, wherein the number of pulses is 600-1200; Preferably, the pulse laser deposition method in step (5) is carried out under the following conditions: the energy density of the pulse laser is 120-180 mJ / mm 2 , the laser repetition frequency is 1-8Hz.
6. The method according to claim 1, wherein: When 0<P≤2×10 -4 Pa, the prepared lutetium hydride film LuH X It has superconducting properties and there is a superconducting transition between 2.5K and 3K.
7. The method according to claim 1, wherein: When 2×10 -4 Pa<P≤1×10 -3 Pa, the prepared lutetium hydride film LuH X Has metallic properties.
8. The method according to claim 1, wherein: When 1×10 -3 When Pa<P≤1Pa, the prepared lutetium hydride film has semiconductor properties.
9. The method according to claim 1, wherein: When 1Pa<P≤5Pa, the prepared lutetium hydride film has insulating properties.
10. A lutetium hydride film prepared by the method of any one of claims 1 to 9, wherein the composition is represented by the following chemical formula: LuH X , where 0<x≤3.
Citation Information
Patent Citations
Thin film deposition chamber and thin film deposition equipment adopting same
CN202576547U